2020
DOI: 10.1007/s11069-020-04165-8
|View full text |Cite
|
Sign up to set email alerts
|

Perceived attributes of hurricane-related retrofits and their effect on household adoption

Abstract: Understanding how homeowners make protective action decisions is important for designing policies and programs to encourage those actions and community resilience as a whole. This thesis focuses on the role of homeowner perceptions of attributes of the protective actions themselves in influencing household protective action decisions. Specifically, using a combination of revealed and stated preference data from a mailed survey of homeowners in North Carolina, we fitted mixed logit models to predict the probabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Similar to this research, though, Gast et al found cost to be a high barrier (76%). Protection of lives and property has been found as a motivator for fortification by others [68], but only when combined with other factors such as low cost and effort and the belief that the mitigation action added value to the home. Broader benefit-cost ratios may be of less importance to an individual homeowner than to a community but these efforts are broadly cost-effective for hurricanes [69].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this research, though, Gast et al found cost to be a high barrier (76%). Protection of lives and property has been found as a motivator for fortification by others [68], but only when combined with other factors such as low cost and effort and the belief that the mitigation action added value to the home. Broader benefit-cost ratios may be of less importance to an individual homeowner than to a community but these efforts are broadly cost-effective for hurricanes [69].…”
Section: Discussionmentioning
confidence: 99%